Maqashid Sharia Framework for Product Innovation in BMT As'adiyah Sharia Cooperative in the Digital Era - Ahmad Rijal Amiruddin; Samsuddin; Achmad Syawal Nurhidayatullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the application of maqashid syariah as a framework for product innovation at BMT As’adiyah, an Islamic cooperative, in the digital era. The five core principles of maqashid syariah hifdz ad-din (religion), hifdz an-nafs (life), hifdz al-aql (intellect), hifdz an-nasl (lineage), and hifdz al-mal (wealth) serve as the foundation for developing financial products aligned with Islamic values. Using a qualitative approach and a descriptive case study method, data were collected through interviews, observations, and document analysis, then processed using thematic analysis and triangulation techniques. The findings show that digitalization has improved operational efficiency, expanded access to Islamic financial services, and strengthened the protection of maqashid principles. Innovations such as Islamic education savings and digital ZIS (zakat, infaq, and sadaqah) platforms illustrate strategic developments. The study concludes that integrating maqashid syariah with digital technology can enhance the relevance, competitiveness, and social impact of Islamic cooperatives.